The Effect of Social Media on EFL Students’ Motivation in Learning English at UM Bulukumba - Ulfa Damayanti (Lingedu: Journal of Linguistics and Education, 2025)
This study examines the effect of social media on EFL students' motivation in learning English. The purpose of this research is to find out the influence of social media on the students' motivation to learn English. Social media, as used by the researcher, is YouTube, WhatsApp, and TikTok. Research methods used in this research are a descriptive research method with a quantitative approach, with data collection techniques using a closed questionnaire with a Google form. The number of samples in this study was 20 students in class 18. A member of the Department of English Education at Muhammadiyah University of Bulukumba. Data collection in this study uses 3 instruments, namely questionnaires, interviews, and documentation. The results showed that the agree option has a percentage value of 42% and the option strongly agrees 20%. This percentage value is in the 41-60 level in the moderately influential category, and it can be defined that most English education students class 18. At the Muhammadiyah University of Bulukumba use social media, one of which is to learn English and to increase their motivation in learning. For the Neutral option, the percentage is quite high, namely 30% and is in the 21-40 category, which is less influential, and it can be said that using social media for a certain time and activity can reduce students' motivation to learn English using social media. Meanwhile, the disagre value is 6% and strongly disaggregated 2% is in the 0-20% category, which is not influential. It can be concluded that social media, in this case, YouTube, WhatsApp, and TikTok, has an Effect on students' motivation in learning.